THE STRATEGY OF POLITENESS IN NOVEL BORN IN ICE: A LINGUISTIC AND CONTEXTUAL ANALYSIS - Atiq Aqiqotul Hasanah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study analyzes the politeness strategies in Nora Roberts' novel Born in Ice. The analysis uses Brown and Levinson's theory of politeness. A qualitative content analysis method was employed. Data were collected through documentation techniques by reading and recording dialogues and character actions that reflect politeness strategies. The analysis involved classifying both positive and negative politeness strategies, analyzing linguistic elements such as mood and modality through the Systemic Functional Grammar approach, and contextualizing the data based on interpersonal relationships (family, friendship, professional). The results revealed that positive politeness fosters empathy and strengthens interpersonal relationships, while negative politeness maintains harmony and respects individual autonomy in conflict situations. The situational context plays a crucial role in determining the politeness strategies used. This study contributes to the cross-disciplinary field of pragmatic linguistics and popular literature, expanding the understanding of politeness as a communication tool that reflects cultural values and social norms.